Voluntary bankruptcy as preemptive persuasion - Nikolay Dinev (Institute for Advanced Studies (IHS), 2017)
This paper examines the phenomenon of management-initiated, court-supervised reorganization of companies in U.S. bankruptcy court. The proposed in-court persuasion mechanism reconciles excessive reorganizations of non-viable companies (and subsequent repeat failures) with management-initiated filings and a judge who aims to always take appropriate action. In the model, management makes a preemptive voluntary filing to retain control of the process, and thereby engage in a game of Bayesian Persuasion with asymmetric information vis-à-vis the judge. This mechanism endogenously results in the reorganization of some non-viable companies, and exclusively management-initiated (i.e., voluntary) bankruptcy filings. This paper, therefore, explains why non-viable companies could be permitted to reorganize and why there are repeat offender firms that enter bankruptcy multiple times.
Keywords: C72; D21; D72; D82; D83; G33; K20; K40; 330; Bayesian Persuasion; Bankruptcy; Chapter 11; Asymmetric Information